TQM-Based Classroom Management in Improving the Quality of Education at MTsN 1 Serang City, Banten - Subekhan, Moch.; Suryapermana, Nana (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Improving the quality of education is essential for educational institutions to maintain relevance amidst increasing competition and the rapid development of science and technology. One approach is implementing classroom management based on Total Quality Management (TQM). TQM is a management approach focused on quality, involving the participation of all human resources, and aimed at long-term success through customer satisfaction, benefiting all organization members. This study explores the planning, implementation, challenges, solutions, and outcomes of TQM-based classroom management at MTsN 1 Serang City, Banten. A qualitative descriptive approach was used, with data collected through observation, interviews, and documentation. Informants included the headmaster, teachers, and administrative staff. The study found that TQM-based classroom management involved forming a team responsible for student placement and monitoring class activities. Challenges identified included inconsistent program execution, lack of team cohesion, and incomplete application of training outcomes. Solutions proposed include establishing a quality control task force and fostering strong team cohesion. The results indicated improved teaching and learning processes, harmonious relationships among staff, students, and parents, and increased student motivation and achievement, improving education quality.